2022
DOI: 10.1136/oemed-2021-107429
|View full text |Cite
|
Sign up to set email alerts
|

Internet solicitation linked to enhanced occupational health and safety outcomes among sex workers in Metro Vancouver, Canada 2010–2019

Abstract: ObjectivesExamine the independent association between online solicitation and sex workers’ (SWs’) occupational health and safety (OHS), particularly violence and work stress.MethodsData were drawn from a cohort of women SWs (N=942, 2010–2019) in Vancouver, Canada. Analyses used descriptive statistics and bivariate and multivariable logistic and linear regression using generalised estimating equations (GEE); explanatory and confounder modelling approaches were used.Results33.9% (n=319) of participants solicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Our study revealed a high prevalence (33.4%) of online commercial sex-seeking among FSW in China, which aligns with ndings from Canada [11] and Sweden [19], but exceeds the reported rates in Kosovo [12] and England [20]. This high prevalence may be attributed to the widespread popularity and discreet nature of the internet, which facilitates the ease of nding sexual partners.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our study revealed a high prevalence (33.4%) of online commercial sex-seeking among FSW in China, which aligns with ndings from Canada [11] and Sweden [19], but exceeds the reported rates in Kosovo [12] and England [20]. This high prevalence may be attributed to the widespread popularity and discreet nature of the internet, which facilitates the ease of nding sexual partners.…”
Section: Discussionsupporting
confidence: 77%
“…FSW represent a high-risk group for HIV/STD transmission worldwide [1]. Online commercial sex-seeking further contributes to the escalating STD epidemic among FSW [11]. Our study aimed to shed light on the prevalence of online commercial sex-seeking among Chinese FSW and explore associated factors, thus expanding the existing literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of research now exists documenting the adoption of the internet by contact sex workers in industrialized democracies (Argento et al 2018;Minichiello, Scott, and Callander 2013;Sanders et al 2018;Sanders, Connelly, and King 2016) and strategies used by contact sex workers who advertise online to enhance occupational health and safety (Bernier et al 2021;Bungay and Guta 2018;Cunningham and Kendall 2010;Jiao, Bungay, and Jenkins 2021;Kille et al 2017;Kolar, Atchison, and Bungay 2014;Machat et al 2022;Strohmayer, Clamen, and Laing 2019). However, most of this research is based on questionnaire and interview data from relatively small sample populations or small collections of websites or online ads.…”
Section: Introductionmentioning
confidence: 99%
“…As a safety strategy, advertising online significantly reduces risk (Argento et al 2018;Machat et al 2022;Sanders et al 2018) and in industrialized democracies, web and telecommunications technologies have become the dominant way in which workers interact with clients. Contact sex workers who advertise online employ multiple strategies to improve occupational health and safety.…”
Section: Introductionmentioning
confidence: 99%